2006
DOI: 10.1002/psp.414
|View full text |Cite
|
Sign up to set email alerts
|

Describing and projecting the age and spatial structures of interregional migration in Italy

Abstract: A multiplicative component model is applied in this paper to present a simple, yet powerful, framework for analyzing and projecting internal migration flows. The multiplicative components are useful for identifying important underlying structures in the migration patterns. To demonstrate, seven periods of age-specific interregional migration in Italy (1970-1971 to 2000-2001) are analyzed. This information is then used to project the age and spatial structures forward to the 2010-2011 period. The projection mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Also, the two‐way interaction model produced estimates that were nearly indistinguishable from the observed values in the complete ODAS table. Our model preference also supports Raymer et al (2006) and Raymer and Rogers (2007), who found that the three‐way interaction term between origin, destination, and age does not contribute much beyond the two‐way interaction models, except in very specific origin–destination flow cases, for example, those with a very pronounced retirement peak. That is, most of the age patterns of origin–destination‐specific migration are captured by the age patterns exhibited by the total in‐migration and out‐migration flows.…”
Section: A Log‐linear Model For Combining Datasupporting
confidence: 89%
“…Also, the two‐way interaction model produced estimates that were nearly indistinguishable from the observed values in the complete ODAS table. Our model preference also supports Raymer et al (2006) and Raymer and Rogers (2007), who found that the three‐way interaction term between origin, destination, and age does not contribute much beyond the two‐way interaction models, except in very specific origin–destination flow cases, for example, those with a very pronounced retirement peak. That is, most of the age patterns of origin–destination‐specific migration are captured by the age patterns exhibited by the total in‐migration and out‐migration flows.…”
Section: A Log‐linear Model For Combining Datasupporting
confidence: 89%
“…In those countries where the transitions appear less closely tied to migration, contextual factors such as economic development, social inequalities, degree of gender equity, cultural norms, and value systems may shape the structure of the life course and influence its interaction with migration. Period effects may also disrupt migration norms, but available evidence suggests that migration age profiles remain relatively stable over time, or experience a gradual aging of the migration peak (Brown et al 2006;Ishikawa 2001;Raymer, Bonaguidi, and Valentini 2006). Assessment of the extent to which long-term changes in the age structure of migration within individual countries are associated with alterations in the life course-for example, the progressive extension of education to older ages and the delay in union and family formation-would also help establish the significance of life-course transitions in shaping migration.…”
Section: Discussionmentioning
confidence: 99%
“…can be explained by the 1935-1940 table, and 52% of it can be explained by the 1975-1980 table" (p. 336-37). A deeper analytical examination of this issue appears in a sequence of recent papers offering a formal defi nition of what constitutes the age and spatial structures of migration and how they can be represented by a multiplicative log-linear modeling framework (Raymer, Bonaguidi, and Valentini 2006;Rogers, Willekens, and Raymer 2001, 2002, 2003Rogers, Willekens, Little, and Raymer 2002). This article adds to that research in two ways.…”
Section: Describing and Estimating The Age And Spatial Structures Of mentioning
confidence: 93%
“…Furthermore, the modeling framework presented in this paper can be applied to unknown situations. For example, the multiplicative component approach has been applied to project future age-specifi c interregional migration fl ows in Italy (Raymer et al 2006) and to estimate age-specifi c international fl ows between countries in the European Union, Iceland, Norway, and Switzerland during the 2001-2002 period (Raymer forthcoming).…”
Section: The Log-linear Modelmentioning
confidence: 99%